ANALISIS PENDEKATAN MIMETIK DALAM NOVEL TRILOGI PINGKAN MELIPAT JARAK KARYA SAPARDI DJOKO DAMONO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN SASTRA - Arinda Rahmawati; I Nyoman Diarta; A.A. Rai Laksmi (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2022)
Literary work is a reflection of the author from the life of reality. Literature in people's lives has various functions. The problem of this research is how social and cultural facts that occur in real life with those that occur in novels with a mimetic approach. and its support for literary learning. The purpose of this research is to find out the social and cultural facts that occur in the novel Pingkan Mefold Distance by Sapardi Djoko Damono's work with those that occur in the real world and their interactions with literary learning. The scope of this research is to describe the social and culture in the real world with what happens in the novel and its attraction to learning. The benefits of this research can be used as a reference in conducting research related to mimetic studies. The theory that underlies this research is (a) the notion of novel, (b) the notion of literature, (c) the notion of mimetics, (d) social and cultural facts. Data collection was carried out using a qualitative descriptive method. The steps of data collection in this research are reading, understanding, taking notes, classifying, triangulating, and reducing data. The method of data analysis in this study is to present the data and conclude the data. The results of the research on the novel Pingkan Folding the Distance by Sapardi Djoko Damono contained thirtysix data, including the reality of social and cultural life. In the analysis of how to describe social and cultural life in life in the novel, which is then analyzed according to life that occurs in real life. An example of the reality of social life is Toar likes to blush when he talks all kinds of things about the world of fairies, donyan leuntung, the world of spirits that are believed to exist by the Javanese. A cultural example, Onarigami, sounds like it's disconnected. Paying attention and remembering lectures on the concept of derivatives from Japan. The implications of the results of the Pingkan Mefold Distance novel research in the literary learning process as it should be in language learning and literary learning are interrelated. The implications of the results of data analysis on social and cultural facts can give us a picture of the real social and cultural life. In addition, there are many examples that can be taken from the story of this novel, especially regarding the character values contained in it. Regarding the two cultures of Java and Japan, there are signs of each other's life. To literary connoisseurs, take advantage of the good life in the novel.